2007
DOI: 10.1111/j.1525-142x.2007.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Apical organs in echinoderm larvae: insights into larval evolution in the Ambulacraria

Abstract: The anatomy and cellular organization of serotonergic neurons in the echinoderm apical organ exhibits class-specific features in dipleurula-type (auricularia, bipinnaria) and pluteus-type (ophiopluteus, echinopluteus) larvae. The apical organ forms in association with anterior ciliary structures. Apical organs in dipleurula-type larvae are more similar to each other than to those in either of the pluteus forms. In asteroid bipinnaria and holothuroid auricularia the apical organ spans ciliary band sectors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 48 publications
5
122
2
Order By: Relevance
“…There is a great diversity in neuron number among larval forms; even among echinoderms, there are potential differences in the size of both the neural proliferative zone and the resulting apical organ. The 96 h sea star apical organ is composed of 30-50 serotonergic neurons located in two broad dorsal ganglia, whereas sea urchins of a comparable larval stage have only eight serotonergic neurons and these are restricted to a small apical pole territory (Byrne et al, 2007). We have previously compared gene expression along the AP axis of the sea star and sea urchin and suggested that although the sea urchin utilizes the same suite of regulatory genes and similar nested expression domains, the domains are extremely compacted in sea urchins compared with sea stars (Yankura et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is a great diversity in neuron number among larval forms; even among echinoderms, there are potential differences in the size of both the neural proliferative zone and the resulting apical organ. The 96 h sea star apical organ is composed of 30-50 serotonergic neurons located in two broad dorsal ganglia, whereas sea urchins of a comparable larval stage have only eight serotonergic neurons and these are restricted to a small apical pole territory (Byrne et al, 2007). We have previously compared gene expression along the AP axis of the sea star and sea urchin and suggested that although the sea urchin utilizes the same suite of regulatory genes and similar nested expression domains, the domains are extremely compacted in sea urchins compared with sea stars (Yankura et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This grouping reflects both molecular and morphological shared characters, especially the homologies of the ciliated feeding larvae, that is, the dipleurula larva (Hart, 1994;Nielsen, 1999;Strathmann and Bonar, 1976). In particular, a noteworthy shared anterior structure is the presence of a serotonergic nerve net in the anterior apical tuft of some echinoderm larvae (Byrne et al, 2007) and hemichordate tornaria larvae (Dautov and Nezlin, 1992;Nezlin and Yushin, 2004). Although echinoderm and hemichordate dipleurula larvae share many homologies, the larvae of ptychoderid hemichordates have two prominent eyespots in the tornaria larvae, which disappear as metamorphosis proceeds (see Fig.…”
Section: Evolution Of Eyespots In Deuterostome Larvaementioning
confidence: 99%
“…If we accept the sister group relationship of echinoderms and holothurians, this in turn suggests that the larval skeleton was not a plesiomorphy of these two taxa and thus unlikely to be a plesiomorphy of any possible clade including the ophiuroids. Other authors have argued on morphological grounds that the two kinds of plutei are convergent forms [42,43], but as the defining feature of the pluteus is its skeleton, most desirable would be a comparison of the fine details of the developmental genetics responsible for initiating production of the larval skeletons, which we would expect to more exactly overlap in homologous plutei. We emphasize that such evidence would be useful for ruling out the scenario of a single origin for the pluteus within cryptosyringids (electronic supplementary material, figure S3c), not for distinguishing between the dual origin scenarios-however, our molecular evidence clearly favours the Asterozoa (i.e.…”
Section: (B) Asterozoa and The Origins Of The Larval Skeletonmentioning
confidence: 99%